From bombing to social media: The role of returning foreign fighters in nurturing terrorism in Asian countries - Wasisto Jati (SIMULACRA: JURNAL SOSIOLOGI, 2021)
This article aims for revisiting the terrorism studies from different perspective. The terror attacks itself cannot be hundred percent zero but it just fluctuated trend. More specifically, terrorism always adaptive in following trends. While terror attacks still to target innocent civilians, the perpetrators could be closest relatives and neighbors. The way terror attack to reach out that group of people basically shows the silent role of returning foreign fighters (RFF)/returnees nurturing dan breeding terror ideologies. By using critical literature review especially historical narrative analysis, this study wants to examine the current terror trend that utilizes social media. It can spread terror narration and also affecting people to join. The way to analyze data is making clear connection from each literature. The findings of this study are: the RFF is adept at social media in nurturing terror ideologies and then making their home country and new terrorist cells to be breeding grounds.